Characterization of plant growth promoting bacteria isolated from rhizosphere of tomato cultivated in Sikkim Himalaya and their potential use as biofertilizer - Sushmita Chhetri; Mingma Thundu Sherpa; Laxuman Sharma (Scientific Reports)
Abstract The rhizosphere hosts a diverse group of beneficial bacteria that can serve as an alternative to chemical fertilizers. Exploring the potential traits of these bacteria can lead to sustainable farming practices, promoting crop yields while minimizing environmental impact. The present study was conducted to characterize and identify native plant growth-promoting bacteria (PGPB) from the rhizosphere of tomato plants cultivated in the organic state of Sikkim, India. Seventy bacterial strains were isolated from different tomato cultivation sites in Sikkim and characterized for their plant growth-promoting (PGP) traits. Out of these, eight potential bacterial strains were selected, and identified as Klebsiella variicola AST1, Bacillus cereus AST3, Enterobacter sichuanensis AST4, Enterobacter mori KH2, Bacillus cereus SG1, Enterobacter sichuanensis SG2, Enterobacter asburiae YG1, and Priestia aryabhattai YG2. Among them, Enterobacter sichuanensis AST4 demonstrated notable ammonia production (55.14 ± 0.03 mM), phosphate solubilization (564.6 ± 0.19 µgmL–1), and nitrogen fixation potential. Similarly, Klebsiella variicola AST1 exhibited the highest indole-3-acetic acid (IAA) production (125.33 ± 0.2 µgmL–1) during in vitro experiments. Likewise, Enterobacter sichuanensis SG2 displayed substantial gibberellic acid (GA3) production (18.3 ± 0.02 µgmL–1), and siderophore production (85%), against the uninoculated control. Greenhouse experiments further revealed that Klebsiella variicola AST1 significantly improved agronomic performance, with increases in plant height (70%), root length (86%), number of leaves (36.6%), and fresh and dry root weight (77% and 58.3% respectively), compared to the uninoculated control. These findings underscore the potential of rhizospheric bacteria from Sikkim’s organic tomato fields to enhance plant growth and agricultural productivity, promoting a sustainable crop production system.